Early cinema, Sergei Eisenstein, and film culture today: An interview with Ian Christie on new directions in film history - Hagener, Malte and van den Oever, Annie (NECSUS. European Journal of Media Studies 7 (2), 3–21. DOI: http://dx.doi.org/10.25969/mediarep/3445., 2018)
An interview with Ian Christie, conducted by Annie van den Oever and Malte Hagener, on his career and most important topics of research. The interview focuses mainly on his work on Eisenstein and early cinema. It discusses the diverse paradigms and different approaches that have been shifting over the decades. It also reflects on the changes in film studies since the 1970s.
https://katalog.adlr.link/Record/finc-170-4214